Informed Consent (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2024)
Informed consent is the acceptance of a medical intervention by a patient, freely, voluntarily and consciously, after the doctor has informed him or her of the nature of the intervention with its respective risks and benefits. Among the functions of informed consent: Promote the autonomy of individuals, encourage rationality in medical decision- making, protect patients and experimental subjects, avoid fraud and coercion, encourage self-evaluation and self-examination of medical professionals. reduce misgivings and alleviate fears, that is, defend the patient, the professional and the institution.The document must be signed by the patient, as long as he or she has the capacity to make decisions, and it must be done when he or she has understood the information received. In the particular case of minors, they are in a position of limited autonomy with dependence on third parties and mainly, it is the parents who will decide for the purpose of any medical procedure.
Keywords: Informed consent